The experience, satisfaction, and Emergency Department utilization of pediatric patients with sickle cell disease during the Covid-19 pandemic - Alexandra Kirsch; Nataly Apollonsky (The Beryl Institute, 2021)
The COVID-19 pandemic has influenced how patients utilize healthcare. This study examines the utilization, experience, and satisfaction of patients with Sickle Cell Disease (SCD) in the pediatric Emergency Department (ED) during the COVID-19 pandemic compared to the care they had received before the pandemic. The authors surveyed fifty-eight participants ages 14 months to 20 years who presented to the ED for a complaint related to their SCD during the COVID-19 pandemic. The study analyzed five variables: race, SCD severity, hemoglobin (Hgb) genotype, who completed the questionnaire (patient versus parent/guardian), and whether the ED visit resulted in an admission to the hospital. Our results suggest that the COVID-19 pandemic significantly affected the decision of some patients as to whether and when to go to the ED. African Americans and those with severe disease did not wait longer than usual to go to the ED, possibly because these groups are more likely to have more serious and more frequent pain crises. Thus, their decision to present to the ED was driven more by their relatively worse symptoms, rather than such external factors as the pandemic. However, the pandemic did not significantly affect patients' satisfaction with their ED visit or their baseline SCD symptoms. To our knowledge, this is the first study of how the COVID-19 pandemic has affected patients' utilization of, experience in, and satisfaction with a pediatric hospital ED. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.